Geoengineering in the anthropocene through regenerative urbanism - Thomson, G.; Newman, Peter (2016)
Human consumption patterns exceed planetary boundaries and stress on the biosphere can be expected to worsen. The recent "Paris Agreement" (COP21) represents a major international attempt to address risk associated with climate change through rapid decarbonisation. The mechanisms for implementation are yet to be determined and, while various large-scale geoengineering projects have been proposed, we argue a better solution may lie in cities. Large-scale green urbanism in cities and their bioregions would offer benefits commensurate to alternative geoengineering proposals, but this integrated approach carries less risk and has additional, multiple, social and economic benefits in addition to a reduction of urban ecological footprint. However, the key to success will require policy writers and city makers to deliver at scale and to high urban sustainability performance benchmarks. To better define urban sustainability performance, we describe three horizons of green urbanism: green design, that seeks to improve upon conventional development; sustainable development, that is the first step toward a net zero impact; and the emerging concept of regenerative urbanism, that enables biosphere repair. Examples of green urbanism exist that utilize technology and design to optimize urban metabolism and deliver net positive sustainability performance. If mainstreamed, regenerative approaches can make urban development a major urban geoengineering force, while simultaneously introducing life-affirming co-benefits to burgeoning cities.